A presumptive case of gluten sensitivity in a border terrier: a multisystem disorder?. (3rd December 2016) - Lowrie, M.; Hadjivassiliou, M.; Sanders, D. S.; Garden, O. A.
Abstract : Paroxysmal gluten‐sensitive dyskinesia (previously termed canine epileptoid cramping syndrome) is a condition of Border terriers in which the leading manifestation is neurological. The authors describe a case they believe to represent the first report of a Border terrier with a combination of neurological signs, atopy, positive serological results for anti‐transglutaminase 2 (TG2 IgA) and anti‐gliadin (AGA IgG) antibodies, and signs suggestive of gastrointestinal disease with pathological changes in the gastrointestinal tract—seemingly responsive to a gluten‐free diet. As such, the authors suggest that gluten sensitivity in Border terriers may manifest as a multisystem disease in a similar manner to that seen in human beings.